Ex-vivo inhibition of uterine contractility by the stem bark extracts of Omphalocarpum procerum P.Beauv. (Sapotaceae) in mouse models - Enitome Bafor; Tosan Eyegbagharen; Ejiro Ochoyama; MacDonald Idu (GarVal Editorial Ltda., 2020)
Context: The plant Omphalocarpum procerum is used traditionally in Africa to manage female reproductive health issues such as infertility and menstrual cycle regulation. In the search for new therapies for the management of female reproductive issues, the plant O. procerum was investigated in this study. Aims: To determine the activity of the methanol extract of O. procerum stem bark (MOPS) on uterine contractility, as a measure to determine its usefulness in uterine contractility associated disorders. Methods: MOPS' activity on spontaneous, oxytocin, KCl-induced contractions and in calcium-free solution was determined on the isolated uterus. Possible mechanisms of activity were determined using receptor and channel blockers. Results: MOPS inhibited spontaneous and oxytocin-induced contractions. MOPS also inhibited oxytocin-induced contractions in calcium-free solution. MOPS was also found to exert its inhibitory effect through interaction with β-adrenoceptors in the uterus. Conclusions: MOPS has been shown to inhibit uterine contractility in the non-pregnant and pregnant uterus primarily through the activation of β-adrenoceptors in the uterus.